The Effects of Various Weighted Implements on Baseball Swing Kinematics in Collegiate Baseball Players. Issue 5 (May 2019) - Williams, Charles C.; Gdovin, Jacob R.; Wilson, Samuel J.; Cazas-Moreno, Vanessa L.; Eason, John D.; Hoke, Elizabeth L.; Allen, Charles R.; Wade, Chip; Garner, John C.
Abstract : Abstract: Williams, CC, Gdovin, JR, Wilson, SJ, Cazas-Moreno, VL, Eason, JD, Hoke, EL, Allen, CR, Wade, C, and Garner, JC. The effects of various weighted implements on baseball swing kinematics in collegiate baseball players. J Strength Cond Res 33(5): 1347–1353, 2019—The purpose of this study was to investigate the effects of different warm-up (WU) devices on bat swing parameters including maximal resultant velocity (MRV), resultant velocity at ball contact (RVBC), time difference between MRV and RVBC, bat angle at MRV, bat angle at RVBC, and perceptual differences of each WU implement used by National Collegiate Athletic Association Division-I baseball players. Fifteen varsity baseball players completed 1 experimental session during fall training. Retroreflective markers were placed on the bat and tee to measure basic bat kinematics during the swing. Participants completed a general calisthenics WU before being counter-balanced into 1 of 4 WU conditions: standard bat (SB) (33 in/30 oz), fungo (10.6 oz), weighted gloves with SB (weighted gloves) (55.6 oz) and donut with SB (donut) (55.6 oz). Each participant was asked to perform their normal on-deck routine over a 2-minute period, finishing with 5 practice swings with the designated condition. After completion of the WU, a 1-minute rest period (simulating normal game conditions) was given to allow each participant to get set to perform 5 maximal swings with a SB. Five, 1 × 4 (group × condition) repeated measures analysis of variance examined the aforementioned variables. There were no significant differences in MRV, RVBC, time difference between MRV and RVBC, and bat angle at MRV and RVBC between all WU conditions. If presented with the current options, athletes should choose the WU implement with which they are most comfortable using before an at-bat situation.